Designing a 3D Printed Model of the Skull-Base: A Collaboration Between Clinicians and Industry. (March 2022) - Saleh, Youssuf; Piper, Rory; Richard, Michael; Jeyaretna, Sanjeeva; Cosker, Thomas
Introduction: The role of three dimensional (3D) printing in neurosurgical education is becoming increasingly common. Notably, 3D printing can simulate complex anatomical pathways that may be difficult to regularly and accurately reproduce in cadavers. One such example is the course of the facial nerve within the temporal bone and its relation to the labyrinth. This can aid pre-surgical planning and minimise surgical complications. Here we aim to develop a novel anatomically accurate model of the skull base which demonstrates key neuro vascular components and the course of the facial nerve within the temporal bone by developing a 3D printed model of the skull-base that can be used for medical education and pre-surgical planning. Materials and Methods: We utilised a combination of Computed Tomography (CT) and angiography scans to reconstruct the skull base and its vascular contents. Neural components were digitally incorporated under the guidance of the Oxford neurosurgical team and the anatomy department. The model was integrated and printed using polymer jetting. Results: The model was successfully printed, with all neurovascular components included. Notably we were able to highlight the intra-temporal course of the facial nerve by creating a bony window within the temporal bone. Conclusion: Through a collaboration with industry and a multidisciplinary team, we were able to reproduce the base of the skull from patient neuro-imaging. Our model is both cost-effective, reproducible and can aid both medical students and neurosurgical trainees in their training/education.